Digital modeling - Vaughan, William , 1943- (New Riders, 2012)
"Professional modeling is the foundation of every aspect of the 3D production pipeline and is essential to the success of any 3D computer graphics project. [Digital] Modeling is unlike any other modeling book you've seen--it gets to the core of what it takes to create efficient production-ready models and demystifies the process of producing realistic and jaw-dropping graphics. Taking a software-neutral approach, it teaches you the essential skills and concepts that you can apply to modeling in any industry 3D software, such as 3ds Max, LightWave 3D, Maya,Modo, Silo, XSI, ZBrush and other leading programs. Modelers, animators, texture artists, and technical directors can all benefit from the valuable information covered in this jam-packed guide containing years of industry knowledge. Simply put, if you work in 3D, you must have this book."-- Publisher's presentation